Traceability of gas flow measurements in complex distribution systems − uncertainty approach vs error approach - Džemić, Zijad; Širok, Brane; Drnovšek, Janko (Metrology and Measurement systems, 2019)
The objective of the paper is to analyse traceability issues in real-life gas flow measurements in complex distribution systems. The initial aim is to provide complete and traceable measurement results and calibration certificates of gas-flow meters, which correspond to specific installation conditions. Extensive work has been done to enable a more credible decision on how to deal in particular situations with the measurement uncertainty which is always subject of a flow meter’s calibration as a quantitative parameter value obtained in laboratory, and with the qualitative statement about the error of an outdoor meter. The laboratory simulation of a complex, real-life distributed system has been designed to achieve the initial aim. As an extension of standardized procedures that refer to the laboratory conditions, the proposed methods introduce additional “installation-specific” error sources. These sources could be either corrected (if identified) or considered as an additional “installation-specific” uncertainty contribution otherwise. The analysis and the results of the experimental work will contribute to more precise and accurate measurement results, thus assuring proper measurements with a known/estimated uncertainty for a specific gas flow installation. Also, the analysis will improve the existing normative documents by here presented findings, as well as fair trade in one of the most important and growing energy consumption areas regarding the legal metrology aspects. These facts will enable comparing the entire quantity of gas at the input of a complex distributed system with the cumulative sum of all individual gas meters in a specific installation.